The Effectiveness of Lapbook in Teaching Reading Comprehension - Aunurrahman Aunurrahman; Fernando Putra; Maliqul Hafis (Jurnal Pendidikan Bahasa, 2022)
This pre-experimental study aimed to determine the effectiveness of the lapbook and its effect on students’ reading comprehension mastery. A cluster random sampling was used to select the participants, the eighth-grade students of MTs Negeri 02 Pontianak. The data was collected by using tests. Try out was conducted to validate the test. The data collected were analyzed using descriptive and inferential statistics to know the process and result caused by the implementation of the wapbook which was elaborated into three main procedures; pretest, treatments, and post-test. The data analysis shows that the lapbook implementation affected the students’ reading comprehension achievement. The mean score from pre-test was 53.51 and the means score of the post-test was 71.89. The calculated data of the t-test confirms that tobtain was higher than ttable, which means that the alternative hypothesis was accepted. Furthermore, the effect size calculation was 1.07 ( 1.00) which indicates the standard effectiveness of the test is categorized as strong effect according to Cohens’ effect size qualification. In summary, the lapbook is significantly effective and encourages the other English teachers to use it to teach reading comprehension.